Performance and knowledge - Devy, G. N.; Davis, Geoffrey V. (London Routledge, 2021)
Part of the series Key Concepts in Indigenous Studies, this book focuses on the concepts that recur in any discussion of nature, culture and society among the indigenous. This final volume in the five-volume series deals with the two key concepts of performance and knowledge of the indigenous people from all continents of the world. With contributions from renowned scholars, activists and experts across the globe